Kvindelige arketyper og kompositorisk sammensmeltning. Om nogle paralleller mellem Blixens fortælling ”De standhaftige slaveejere” og Munchs piktoriale model [Female archetypes and compositional fusion. On some parallels between Blixen's short story “De standhaftige slaveejere” and Munch's pictorial model] - Stahr, Radka (Folia Scandinavica Posnaniensia, 2023)
This article analyses the hitherto unexplored influence of Edvard Munch on Karen Blixen's work. Blixen was a great connoisseur of art and can therefore be assumed to have known Munch's work. In the short story “De standhaftige slaveejere” we find several parallels to the so-called “Munch's pictorial model”, i.e. a set of common features of his work (specifically his expressionist phase). Most striking is the similarity of the characters to those in Munch's painting Kvinden i tre stadier, which Blixen adopts both in terms of their appearance and their archetypal roles. She is particularly inspired by the colour connotations associated with the characters portrayed in the painting, and creates the figure of a beautiful and innocent girl in a white dress accompanied by an ascetic governess in black. Even the male character in Blixen's short story recalls Munch's archetype of the weak, melancholic man who is about to be destroyed by women. We also find a significant parallel in relation to the typical composition in Munch's paintings, where the individual figures are merged into one. Blixen makes use of this composition in the concrete description of the figures in her story; at the same time, on an abstract level, it is possible to interpret both figures as one multidimensional figure.